Prospective pharmacological potential of cryptotanshinone in cancer therapy - Ashif Ahamed; Mahmadul Hasan; Arijit Samanta; Syed Sahajada Mahafujul Alam; Zarnain Jamil; Safdar Ali; Mehboob Hoque (Pharmacological Research - Modern Chinese Medicine, 2023)
Background: Cryptotanshinone (CPT), a Traditional Chinese Medicine (TCM) has recently gained remarkable interest as a potent alternative cancer therapeutic. The sole objective of this review is to accumulate the anti-tumour activity of CPT against major cancers as well as the underlying mechanisms. Methods: This comprehensive review focuses on the experimental outcome of in vivo and in vitro investigations targeting multiple signalling pathways of various cancers and molecular mechanisms involved in hindering cancer growth. Results: CPT targets different cell signalling pathways, transcription factors (STAT1, 3, 4, 5, c-Myc), cellular markers (PD-1, CTLA-4, PDL-1), kinases (Tyrosine kinase such as IGF-1R, Bcr-Abl, Src, JAK, FAK, Serine/Threonine kinase such as Aurora A, Cyclin dependent kinase such as CDK1, 2) which are associated with stemness, growth, division, proliferation, metastasis, angiogenesis and drug resistance of a cancer cell. CPT suppresses cancer progression by inhibiting the phosphorylation of intermediate signalling molecules like STAT3, hence disrupting the STAT3 signalling pathway amongst several other signalling pathways involved in cancer progression. CPT may also induce apoptosis by modulating several pro-apoptotic (Bax, Bak, Bcl-10) and anti-apoptotic (Bcl-2, Bcl-x, Bcl-xL) proteins. Furthermore, CPT showed potential drug synergism with other chemotherapeutic drugs resulting in strategizing better cancer treatment. Conclusion: This review summarizes that CPT, being a natural product with less side-effects in long-term cancer use, may be considered as a potential alternative to the traditional cancer therapies. Although, there is substantial evidence of success in laboratory, its efficacy for clinical application may be increased with an appropriate drug delivery approach and the accurate formulation or dosage.